Dakwah Berbasis Komunitas dalam Pemikiran Emha Ainun Nadjib: Analisis Manajemen Dakwah - Ikhlasud Dafa; Hanik Maimuna; M. Anang Sholikhudin; Eka Nuraulia; M. Afandi Bahrudin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This study seeks to examine the community-based da’wah model from a da’wah management perspective through the ideas of Emha Ainun Nadjib. A qualitative approach with a library research method is employed, utilizing primary sources derived from Emha Ainun Nadjib’s works and supported by relevant scholarly journal articles. Data collection is conducted through documentation, while the analysis applies content analysis using a descriptive-analytical framework. The findings indicate that the community-based da’wah model proposed by Emha Ainun Nadjib is characterized by participatory, dialogical, humanistic, non-hierarchical, and cultural dimensions. These principles are reflected in the practice of the Maiyah community, which functions as an open and egalitarian space for interaction. From the perspective of da’wah management, this model demonstrates alignment with managerial functions, including planning, organizing, actuating, and controlling, although it is not implemented through rigid formal structures. This approach effectively enhances community participation and fosters contextual collective awareness. In conclusion, the community-based da’wah model in Emha Ainun Nadjib’s thought can be considered a relevant contemporary strategy that is adaptive, inclusive, and oriented toward community empowerment.